PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Ika Surya Martsila; Wahyu Meiranto (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of Corporate Governance on firm’s financial performance in non financial firms.Corporate Governance used in this study is independency board commissioner, board size, management ownership, ownership concentration and leverage. This study also used firm size as control variables.Samples of this study were non financial firms listed on Indonesia Stock Exchange for the observation period of 2009 until 2011. Samples were collected by purposive sampling method and resulted 117 samples. This study used multiple regressions for analyzing data.The result revealed thatboard size has significant positive effect on ROA and significant negative effect on PER. Ownership concentration has significant positive effect on ROA and ROE also significant negative effect on PER. Leverage and significant negative effect on ROA, PER and Tobins'Q. The research also found a positive and significant effect between firm size and corporate financial performance proxied by ROA, ROE, PER and Tobins'Q.